Stem Cell-Induced Cell Motility: A Removable Obstacle on the Way to Safe Therapies?. (15th February 2022) - Rosner, Margit; Hengstschläger, Markus
Abstract: It is the hope of clinicians and patients alike that stem cell-based therapeutic products will increasingly become applicable remedies for many diseases and injuries. Whereas some multipotent stem cells are already routinely used in regenerative medicine, the efficacious and safe clinical translation of pluripotent stem cells is still hampered by their inherent immunogenicity and tumorigenicity. In addition, stem cells harbor the paracrine potential to affect the behavior of cells in their microenvironment. On the one hand, this property can mediate advantageous supportive effects on the overall therapeutic concept. However, in the last years, it became evident that both, multipotent and pluripotent stem cells, are capable of inducing adjacent cells to become motile. Not only in the context of tumor development but generally, deregulated mobilization and uncontrolled navigation of patient's cells can have deleterious consequences for the therapeutic outcome. A more comprehensive understanding of this ubiquitous stem cell feature could allow its proper clinical handling and could thereby constitute an important building block for the further development of safe therapies. Graphical Abstract: